Corrosion mechanisms in theory and practice - Marcus, P. (Philippe), 1953- (Corrosion technology (Boca Raton, Fla.), 2012)
"Building on previous editions described as "a useful contribution to the current literature on corrosion science, engineering, and technology" by Corrosion Review, this third installment offers real-world applications and problem-solving techniques to reduce the occurrence of pits, cracks, and deterioration in industrial, automotive, marine, and electronic structures. It also details the electrochemical and chemical properties, adsorption mechanisms, environmental parameters, and microstructural factors that influence corrosion formation. Including contributions from authors around the world, this reorganized third edition covers the most recent advances in the field, adding three new chapters on Fundamentals of Corrosion from a Surface Science and Electrochemical Basis, High-Temperature Oxidation, and Atomistic Modeling of Corrosion"--